Production of Different Biochemicals by Paenibacillus polymyxa DSM 742 From Pretreated Brewers’ Spent Grains - Didak Ljubas, Blanka; Novak, Mario; Trontel, Antonija; Rajković, Ana; Kelemen, Zora; Marđetko, Nenad; Grubišić, Marina; Pavlečić, Mladen; Tominac, Vlatka Petravić; Šantek, Božidar (Frontiers in Microbiology, 2022)
Brewers’ spent grains (BSG) are a by-product of the brewing industry that is mainly used as feedstock; otherwise, it has to be disposed according to regulations. Due to the high content of glucose and xylose, after pretreatment and hydrolysis, it can be used as a main carbohydrate source for cultivation of microorganisms for production of biofuels or biochemicals like 2,3-butanediol or lactate. 2,3-Butanediol has applications in the pharmaceutical or chemical industry as a precursor for varnishes and paints or in the food industry as an aroma compound. So far, Klebsiella pneumoniae, Serratia marcescens, Clostridium sp., and Enterobacter aerogenes are being used and investigated in different bioprocesses aimed at the production of 2,3-butanediol. The main drawback is bacterial pathogenicity which complicates all production steps in laboratory, pilot, and industrial scales. In our study, a gram-positive GRAS bacterium Paenibacillus polymyxa DSM 742 was used for the production of 2,3-butanediol. Since this strain is very poorly described in literature, bacterium cultivation was performed in media with different glucose and/or xylose concentration ranges. The highest 2,3-butanediol concentration of 18.61 g l–1 was achieved in medium with 70 g l–1 of glucose during 40 h of fermentation. In contrast, during bacterium cultivation in xylose containing medium there was no significant 2,3-butanediol production. In the next stage, BSG hydrolysates were used for bacterial cultivation. P. polymyxa DSM 742 cultivated in the liquid phase of pretreated BSG produced very low 2,3-butanediol and ethanol concentrations. Therefore, this BSG hydrolysate has to be detoxified in order to remove bacterial growth inhibitors. After detoxification, bacterium cultivation resulted in 30 g l–1 of lactate, while production of 2,3-butanediol was negligible. The solid phase of pretreated BSG was also used for bacterium cultivation after its hydrolysis by commercial enzymes. In these cultivations, P. polymyxa DSM 742 produced 9.8 g l–1 of 2,3-butanediol and 3.93 g l–1 of ethanol. On the basis of the obtained results, it can be concluded that different experimental setups give the possibility of directing the metabolism of P. polymyxa DSM 742 toward the production of either 2,3-butanediol and ethanol or lactate.